The Influence Of Non-Halal Income And Interest-Based Debt On The Value Of Sharia-Compliant Issuers In The Energy Sector - Rachmat Budiono; Indra Indra; Indra Indra (Faculty of Islamic Business and Management, 2025)
This study investigates the impact of non-halal income and interest-based debt on the value of sharia-compliant issuers in Indonesia’s energy sector—a capital-intensive industry where the use of debt is often inevitable. Prior research has explored the influence of capital structure and Sharia compliance broadly, but studies focusing specifically on the interaction of non-halal income and interest-based debt within the energy sector remain limited. Addressing this gap, the study employs a panel data approach covering 15 energy companies listed on the Indonesia Sharia Stock Index (ISSI) over the period 2018–2022. The Price to Book Value (PBV) ratio is used as a proxy for firm value. The results reveal that non-halal income (PNH) does not significantly affect PBV (p = 0.4684), indicating minimal influence on firm value. However, interest-based debt (UBB) negatively affects PBV at a 10% significance level, suggesting that higher UBB reduces firm value. Moreover, the interaction between PNH and UBB shows a significant negative effect on PBV, implying that a high combination of both variables further decreases firm value. In contrast, Return on Assets (ROA), Return on Equity (ROE), and Earnings Per Share (EPS) have significant positive effects on PBV. These findings highlight the need for greater financial discipline and Sharia compliance among energy sector issuers to maintain investor confidence and firm value.